2001
DOI: 10.1073/pnas.081072398
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -binding activity of a COOH-terminal fragment of the Drosophila BK channel involved in Ca 2+ -dependent activation

Abstract: Mutational and biophysical analysis suggests that an intracellular COOH-terminal domain of the large conductance Ca 2؉ -activated K ؉ channel (BK channel) contains Ca 2؉ -binding site(s) that are allosterically coupled to channel opening. However the structural basis of Ca 2؉ binding to BK channels is unknown. To pursue this question, we overexpressed the COOH-terminal 280 residues of the Drosophila slowpoke BK channel (Dslo-C280) as a FLAG-and His 6-tagged protein in Escherichia coli. We purified Dslo-C280 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
121
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(133 citation statements)
references
References 32 publications
12
121
0
Order By: Relevance
“…At least two high-affinity Ca 2ϩ sensors in each Slo1 polypeptide are known: the RCK1 sensor encompassing D367 (27) and the Ca 2ϩ bowl sensor in the RCK2 domain (28,29). Inspection of the human Slo1 amino acid sequence showed that the putative RCK1 Ca 2ϩ sensor subdomain contains several histidine residues near D367, a critical component of the RCK1 high-affinity Ca 2ϩ sensor (27) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At least two high-affinity Ca 2ϩ sensors in each Slo1 polypeptide are known: the RCK1 sensor encompassing D367 (27) and the Ca 2ϩ bowl sensor in the RCK2 domain (28,29). Inspection of the human Slo1 amino acid sequence showed that the putative RCK1 Ca 2ϩ sensor subdomain contains several histidine residues near D367, a critical component of the RCK1 high-affinity Ca 2ϩ sensor (27) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this guardian role of controlling Ca 2ϩ influx and excitability, BK channels modulate many processes, such as spike broadening in neurons (3), smooth muscle contraction (4), neurotransmitter release (5), and the electrical tuning of hair cells (6,7). The activation of BK channels by Ca i 2ϩ typically occurs with Hill coefficients of 2-5 (1,(8)(9)(10)(11), indicating that Ca i 2ϩ acts in a highly cooperative manner. These coefficients suggest that a minimum of 2-5 Ca 2ϩ must be bound to allosteric activators to maximally activate the channel.…”
mentioning
confidence: 99%
“…1A, C). Partial deletion or point mutations of the aspartates contained in the calcium bowl produced BK channel that were less sensitive to Ca 2+ -at the same Ca 2+ concentration, the calcium bowl mutant conductance-voltage (G-V) curves were right-shifted compared to the wildtype BK channel G-V curve (Schreiber and Salkoff, 1997;Bian et al, 2001;Braun and Sy, 2001). If the Ca 2+ bowl is disrupted by deleting crucial aspartates, this high Ca 2+ affinity regulatory site is lost, but the mutant and the wild-type BK showed the same sensitivity to Cd 2+ ions.…”
Section: Sensing Elementsmentioning
confidence: 99%
“…The D5N5 mutant expressed in cells exhibits a lower Ca 2+ sensitivity for activation and reduces the dSlo channel's Hill coefficient 2-fold, as if one binding site per monomer is lost in the D5N5 mutant. The most economic way to account for these results is to assume the existence of two distinct Ca 2+ -binding sites per channel monomer (Bian et al, 2001;cf. Schreiber and Salkoff, 1997).…”
Section: Sensing Elementsmentioning
confidence: 99%
See 1 more Smart Citation